Application of 3D Printing Techniques in Modern Infrastructure Development Mela Amelia Santika - Shanshan Xu; Wolnough Cale; Mahon Nitin (Journal of Moeslim Research Technik, 2024)
Modern infrastructure development faces complex challenges in terms of speed, cost and sustainability. In an effort to meet these demands, 3D printing techniques have emerged as a promising innovative solution. However, there are still few studies that comprehensively examine the application of 3D printing techniques in the context of modern infrastructure development. This research aims to explore the potential application of 3D printing techniques in modern infrastructure development and to provide a deeper understanding of its benefits, challenges and practical implications. The research methods used include an in-depth literature study, case analysis, and interviews with relevant experts and practitioners. This approach allows us to have a holistic understanding of how 3D printing techniques can be applied in modern infrastructure development. The results show that the application of 3D printing techniques in modern infrastructure development has significant potential in terms of construction efficiency, design flexibility, and material waste reduction. However, there are still some challenges that need to be overcome, such as limited materials and standards, and limited availability of technology. Overall, this study concludes that 3D printing techniques have great potential to change the paradigm of modern infrastructure development. However, to fully realize this potential, cross-sectoral cooperation, investment in research and development, and the development of adequate regulations are required to overcome the challenges faced.